2016
DOI: 10.1017/s0263574715000983
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure of a biped walking robot: instantaneous and degree-of-freedom-based instrumentation with human gait implications

Abstract: SUMMARYEnergy expenditure (EE) is an important criterion for design and control of biped walking robots. However, the cause-effect analyses enabled by total EE, which is lumped over a time duration and all system degrees-of-freedom (DOFs), are limited. In this study, robotic gait energetics is evaluated through a DOF-based instrumentation system designed for instantaneous evaluation of bidirectional current and applied voltage at each joint actuator. The instrumentation system includes a dual-module arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The high energy consumption at low velocities has been reported for both humans and robots. In their study, Roberts et al 35 present experimental results where the energy consumption at 0.025 m/s was nine times higher than that at 0.15 m/s. Another reason explaining the high COT obtained is the compliance margin and slope of the servomotors, which were configured to their maximal values to guarantee a precise tracking of the reference trajectory.…”
Section: The Cost Of Transportationmentioning
confidence: 95%
See 3 more Smart Citations
“…The high energy consumption at low velocities has been reported for both humans and robots. In their study, Roberts et al 35 present experimental results where the energy consumption at 0.025 m/s was nine times higher than that at 0.15 m/s. Another reason explaining the high COT obtained is the compliance margin and slope of the servomotors, which were configured to their maximal values to guarantee a precise tracking of the reference trajectory.…”
Section: The Cost Of Transportationmentioning
confidence: 95%
“…This is because during the experimentation we could not guarantee that the robot would walk on a perfect straight path, and as a consequence, the distance traveled by the robot was different from 0.75 m. Our COVs are consistent with those reported in similar experiments. In their study, Roberts et al 35 reported COVs ranging from 5.9% to 12.4% for the energy expenditure of the DARwIn-OP humanoid robot. In the study by Ogura et al, 45 the electrical energy expenditure of the WABIAN robot is measured for three walking styles and two different step lengths (a total of six experimental configurations).…”
Section: The Sources Of Variabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…Robotized gantry cranes, for moving containers, or biped robots for manipulation tasks, such as lifting and carrying heavy weights, are being adopted mainly for high volume handling. Within these applications, biped robots are required to satisfy not only the power requirements [4], but also advanced balancing and locomotion capabilities [5,6], which are critical for carrying loads [7] and that are required to physically interact with the human-made environment [8,9,10]. There are many elements that affect the efficiency of containers flow.…”
Section: Introductionmentioning
confidence: 99%